Prospects for Small Hydropower in Ukraine in the Context of Feasibility and Environmental Impact: Summarising after the World Small Hydropower Development Report 2022 (Моделювання, керування та інформаційні технології, 2025)
The use of renewable energy and decentralization of energy generation in Ukraine has become a crucial and topical problem because of the war and devastating russian enemies’ attacks on the Ukrainian critical energy infrastructure. Localized renewable energy generation stimulates humanitarian engineering that can support community peace-sustainability. However, before decision-making, appropriate resources and opportunities should be analyzed. An optimal way for a local energy generation portfolio development has to include a comprehensive feasibility analysis of projects accounting for key enablers and barriers and a full-fledged holistic environmental impact analysis of proposed technologies. At the same time, unworthy speculations touching people suffering have to be excluded, especially on the side of investors interested in the profits of the feed-in tariff.   This article analyzes prospects for small hydropower in Ukraine in the context of its feasibility and environmental impact. The principal aim of the article is to answer the two questions. The first one is whether small-scale hydropower in Ukraine can principally pretend to play an essential role in localized renewable energy supply. The second one is whether the environmental impact of small hydropower in the country would be admissible in social and ecological contexts. The article is based on the World Small Hydropower Development Report 2022 materials, primarily regarding Ukraine.